Validity and Effectiveness of a Project-Based Learning E-Module on Virus Topics to Enhance Students’ Creative Thinking Skills - Tutik Ari Murti; Harlita Harlita; Puguh Karyanto (Journal of Educational Sciences, 2026)
This study was designed to evaluate the validity and effectiveness of a PjBL e-module on the virus topic in developing high school students’ creative thinking abilities. The validation of the e-module was carried out qualitatively, while its effectiveness was investigated through a quasi-experimental approach using a nonrandomized control group with pretest and posttest. The population comprised all Grade X students at SMA Negeri 1 Polokarto in the 2025/2026 academic year. Two classes were sampled: X E1 as the experimental group using the PjBL e-module and X E3 as the control group with conventional materials.  The e-module was reviewed by four expert validators covering material, media, language, and instructional aspects. Effectiveness data were examined using an independent sample t-test and N-Gain scores. The validation process indicated a very high level of validity, with an overall average score of 94.38%. The t-test significance value of 0.007 (<0.05) confirmed a significant difference in creative thinking skills between the two groups. N-Gain scores demonstrated moderate improvement, with values of 0.37 for the control class and 0.57 for the experimental class. These results show that the PjBL e-module is valid and effective in enhancing students’ creative thinking skills regarding the virus topic.